1997
DOI: 10.1364/josaa.14.003341
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal-Gaussian beams in complex optical systems

Abstract: Sinusoidal-Gaussian beam solutions are derived for the propagation of electromagnetic waves in free space and in media having at most quadratic transverse variations of the index of refraction and the gain or loss. The resulting expressions are also valid for propagation through other real and complex lens elements and systems that can be represented in terms of complex beam matrices. The solutions are in the form of sinusoidal functions of complex argument times a conventional Gaussian beam factor. In the lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(55 citation statements)
references
References 27 publications
0
55
0
Order By: Relevance
“…In Refs. [9,12] it was pointed out that ChG beams cannot retain their shapes unchanged upon propagation and different beam profiles can be obtained at a certain place by varying the decentered parameter g. Our study has shown that, by an appropriate choice of the spatial coherence parameter b and/or astigmatic coefficient C 6 , the spatial shaping of partially coherent ChG beams is achievable …”
Section: Resultsmentioning
confidence: 67%
“…In Refs. [9,12] it was pointed out that ChG beams cannot retain their shapes unchanged upon propagation and different beam profiles can be obtained at a certain place by varying the decentered parameter g. Our study has shown that, by an appropriate choice of the spatial coherence parameter b and/or astigmatic coefficient C 6 , the spatial shaping of partially coherent ChG beams is achievable …”
Section: Resultsmentioning
confidence: 67%
“…Two concrete examples of seed functions of the modified kind are provided by the cosh-Gaussian beams [17] and the modified Bessel beams [18,19].…”
Section: Classification Of the Generalized Vector Hzg Beamsmentioning
confidence: 99%
“…Casperson and co-workers introduced general solution of the Helmholtz equation, namely, HermiteSinusoidal-Gaussian beams in 1990s [15,16]. ChG beams are regarded as the special case of Hermite-sinusoidalGaussian beams, and are of practical interest because their profiles can be altered by choosing suitable beam parameters in cosh parts [17].…”
Section: Introductionmentioning
confidence: 99%